Association between radical cystectomy prophylactic antimicrobial regimen and postoperative infection - Ross, James Paul Joseph; Breau, Rodney H.; Vigil, Humberto; Hickling, Duane R.; Angel, Jonathan B.; Mallick, Ranjeeta; Cagiannos, Ilias; Morash, Christopher; Lavallee, Luke T. (Canadian Urological Association Journal, 2021)
Introduction: Infections are common after radical cystectomy. The objective of this study was to determine the association between antimicrobial prophylactic regimen and infection after radical cystectomy. Methods: A retrospective cohort study was performed on patients who underwent radical cystectomy at one tertiary Canadian center between January 2016 and April 2020. Patients received antimicrobial prophylaxis based on surgeon preference (cefazolin/ metronidazole or ampicillin/ciprofloxacin/metronidazole, or other). A univariable and multivariable logistic regression model was created to determine the association between antimicrobial regimen and postoperative infection within 30 days. The association between patient demographic factors, as well as preoperative and intraoperative variables and infection, was also determined. Infection characteristics, including type, timing, and antimicrobial susceptibilities were reported. Results: One hundred and sixty-five patients were included. Mean age was 69.8 years, 121 (73.3%) were male, and 72 (43.6%) received orthotopic neobladder diversion. Ninety-six patients (58%) received cefazolin/metronidazole prophylaxis, 50 (30%) received ampicillin/ciprofloxacin/metronidazole, and 19 (11.5%) received another regimen. Fifty-four patients (32.7%) developed a postoperative infection (surgical site infection or urinary tract infection). Surgical site infection occurred in 35 patients (21.2%) and urinary tract infection occurred in 34 (21.0%). There was no association between antimicrobial regimen and incidence of postoperative infection (surgical site infection or urinary tract infection, relative risk 0.99, 95% confidence interval 0.50–1.99). Conclusions: The overall incidence of infection was 32.7% following radical cystectomy. The preoperative prophylactic antibiotic regimen used was not associated with incidence of postoperative infection.